Relationship between pharmacotherapy complexity and patient satisfaction with treatment for hepatitis C - Maria de las Aguas Robustillo-Cortés; Carmen Victoria Almeida-González; Ramón Morillo-Verdugo (Farmacia Hospitalaria)
Objective: To establish the relationship between the complexity of treatment for hepatitis C and patient satisfaction. Method: An observational, prospective, single-center study, which included HCV patients treated between October 2014 and February 2016. The primary endpoint was the assessment of satisfaction with treatment, measured by the HCV-ESTAR questionnaire, structured into two dimensions: clinical and lifestyle satisfaction, on a 0-60 score. A reliability analysis was performed. The data collected were: treatment prescribed for HCV, concomitant medication, and Sustained Viral Response. The complexity index of the complete pharmacotherapy was calculated by the computer application MRCI. T-Student was used to identify the complexity of treatment as a marker of dissatisfaction. Results: The study included 171 patients (83.0% male). The mean satisfaction score was 47.9±7.5. The reliability of the complete questionnaire was high (Cronbach alpha, 0.864; intraclass coefficient, 0.843). There was correlation between the Complexity Index and satisfaction (P<0.05). A reduction of 5 points in the Complexity Index increased fourfold the value of satisfaction with treatment (p<0.0001). Similarly, a reduction in 12 points in the Concomitant Medication Index doubled the satisfaction (p=0.028). Regarding the overall complexity, 10 points less doubled the satisfaction (p<0.05). Finally, patients with higher values of satisfaction presented a higher response rate (p=0.029). Conclusions: An increase in pharmacotherapeutical complexity has an impact on satisfaction, and at the same time, on achieving Sustained Viral Response